2019
DOI: 10.1007/s11423-019-09676-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of software to support argumentative reading and writing by means of creating a graphic organizer from an electronic text

Abstract: This paper describes the development of a software program that supports argumentative reading and writing, especially for novice students. The software helps readers create a graphic organizer from the text as a knowledge map while they are reading and use their prior knowledge to build their own opinion as new information while they think about writing their essays. Readers using this software can read a text, underline important words or sentences, pick up and dynamically cite the underlined portions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 105 publications
(132 reference statements)
0
12
0
1
Order By: Relevance
“…Our previous study [6] showed improvements in individual argumentative reading and writing to some extent; however, there were no opportunities for learners to be exposed to perspectives other than the text author's and the reader's. According to the literature discussed above, we considered that there would be fruitful opportunities in peer response activities using effective computerbased scaffolds for allowing learners to think more critically about their reading and essays.…”
Section: Computer-based Scaffolds For Collaborative Learning To Enhance Critical Reading and Writing Activitiesmentioning
confidence: 88%
See 3 more Smart Citations
“…Our previous study [6] showed improvements in individual argumentative reading and writing to some extent; however, there were no opportunities for learners to be exposed to perspectives other than the text author's and the reader's. According to the literature discussed above, we considered that there would be fruitful opportunities in peer response activities using effective computerbased scaffolds for allowing learners to think more critically about their reading and essays.…”
Section: Computer-based Scaffolds For Collaborative Learning To Enhance Critical Reading and Writing Activitiesmentioning
confidence: 88%
“…One of the promising ways to achieve a desirable level of critical reading is to help learners create node-link representations by making graphic organizers [11], [12] such as concept maps [13] or knowledge maps [14] (for a review, see [15]). Making graphic organizers with node-link representations can help learners build constructive arguments based on their interpretations of the text [6], [16], [17] . In addition, node-link representations also allow researchers to develop a function for communication among learners that helps them take ideas described in their notes to a higher level [18] .…”
Section: Teaching Critical Reading Skills As Constructive and Argumentative Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the findings to consider which features were beneficial and which were not helpful would help in understanding these findings. There were 17 studies in which statistically significant positive effects on at least one learning measure were noted (Asrowi et al, 2019;Chang et al, 2019;Chaudhri et al, 2013;Chen et al, 2014;Chen et al, 2018;Dennis et al, 2016, Ebied 2015Jin, 2013;Hsiao et al, 2016;Jin, 2013;Li et al, 2013;Lustria, 2007;Mochizuki et al, 2019;Sommers et al, 2019;Zarzour & Sellami, 2017;Zarzour & Sellami, 2018a;Zarzour & Sellami, 2018b). Most of these studies with positive effects had multiple interactive features making it challenging to discern the features or combination of features most effective.…”
Section: E-text Interactive Features 13mentioning
confidence: 99%